2017
DOI: 10.1097/qai.0000000000001523
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Inflammatory Colonic Innate Lymphoid Cells Are Increased During Untreated HIV-1 Infection and Associated With Markers of Gut Dysbiosis and Mucosal Immune Activation

Abstract: BACKGROUND HIV-1 infection is associated with intestinal inflammation, changes in the enteric microbiota (dysbiosis) and intestinal epithelial cell (IEC) damage. NKp44+ innate lymphoid cells (ILCs) play an important role in epithelial barrier maintenance via the production of IL-22, but also display functional plasticity and can produce inflammatory cytokines (e.g. IFNγ) in response to cytokine milieu and stimulatory signals. The objective of this pilot study was to enumerate frequencies of IL-22 and IFNγ-expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
0
12
1
Order By: Relevance
“…[16][17][18][19] In the context of HIV, we have reported an increase in IFNγproducing NKp44+ CD56+ ILCs (a population of cells likely to include both NK cells and ILC1s) in the colonic mucosa of people living with HIV (PLWH) who are naïve to treatment. 20 Increases in IFNγ-producing and cytotoxic colonic ILCs (defined as CD3-NKp44+) were also reported in Rhesus macaques infected with SIV (the nonhuman primate model of HIV). 21,22 Conversely, in PLWH on anti-retroviral treatment with viral suppression the percentage of IFNγ-producing ILC1s in the gut mucosa were not different compared to uninfected controls.…”
Section: Introductionmentioning
confidence: 89%
“…[16][17][18][19] In the context of HIV, we have reported an increase in IFNγproducing NKp44+ CD56+ ILCs (a population of cells likely to include both NK cells and ILC1s) in the colonic mucosa of people living with HIV (PLWH) who are naïve to treatment. 20 Increases in IFNγ-producing and cytotoxic colonic ILCs (defined as CD3-NKp44+) were also reported in Rhesus macaques infected with SIV (the nonhuman primate model of HIV). 21,22 Conversely, in PLWH on anti-retroviral treatment with viral suppression the percentage of IFNγ-producing ILC1s in the gut mucosa were not different compared to uninfected controls.…”
Section: Introductionmentioning
confidence: 89%
“…Similarly, reduced frequencies of IL-22/IL-17-producing ILCs during Simian Immunodeficiency Virus (SIV) infection (the non-human primate model of HIV) were noted (2428). Furthermore, we and others have reported increased frequencies of IFNγ-producing ILCs both in people living with HIV (PLWH) who were not receiving anti-retroviral therapy (ART) (29) and during SIV infection (27). Since IFNγ alters epithelial tight junctions and upregulates epithelial cell expression of TNFα receptor which results in further epithelial cell damage (30, 31), increased frequencies of IFNγ-producing ILC3s may be an additional contributor to epithelial barrier breakdown.…”
Section: Introductionmentioning
confidence: 93%
“…When the epithelial barrier is compromised, translocation of gut-associated bacteria into the lamina propria (LP) exposes immune cells to bacteria of different species or magnitude than what these cells typically encounter in the healthy human gut (32, 33). We previously demonstrated that increased frequencies of colonic IFNγ-producing ILCs in PLWH correlated with alterations in mucosa-associated bacterial communities (dysbiosis), specifically with increased relative abundance of Gram-negative commensal Prevotella species (29). Understanding the bacteria-specific cytokine responses of ILC3s and the mechanisms by which protective or deleterious cytokines are produced are critical to determining the effect of ILC3s on gut homeostasis, not only for their role in enteric bacterial immunity, but also for their role in influencing epithelial cell function in disease states.…”
Section: Introductionmentioning
confidence: 99%
“…pooled for same-day flow-based immunophenotyping [50,60] and the rest were frozen for later histology and transcriptomics. The study obtained comprehensive data including gut and PBMC IFNα and IFNβ transcript levels, plasma and gut viral loads, gut CD4+ T cell percentages (of CD45+ cells), myeloid activation (CD40 MFI in CD1c+ myeloid DCs), blood CD4+ T cell counts, markers of microbial translocation (sCD27, LPS, LTA), inflammation (CRP, IL6), and epithelial barrier dysfunction (iFABP) ( Table 1 and S11 Table) [38,50,[60][61][62][63]. We investigated how individual altered core ISGs (n = 126) and IFNβ-specific ISGs (n = 112) correlated with these clinically relevant parameters using linear regression models, after adjusting the data for age and gender.…”
Section: Plos Pathogensmentioning
confidence: 99%